Financial disincentives to formal work: Evidence from Ecuador and Colombia - H. Xavier Jara; David Rodriguez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The aim of this paper is to quantify the financial cost that informal workers would incur in the event of entering formality, accounting for potential earnings gains upon entry. To do so, we use representative microdata from Ecuador and Colombia, together with detailed tax - benefit models, and simulate transitions to formal employment for all workers observed in informality in the data, with informality defined as non-affiliation to social security. Our results point to strikingly high formalization costs in the two countries, with on average 52.8 and 78.5 per cent of workers' additional earnings taxed away due to social security payments in Ecuador and Colombia, respectively. Costs are particularly high for self-employed informal workers at the bottom of the earnings distribution. The results are mainly driven by the requirement that workers contribute to social security at least on the basis of the minimum wage in both countries.
Keywords: J42; H22; H55; 330; formalization tax rate; informality; microsimulation